Inheritance Development and Expiration - Ahmad Nizar Mohammad Syamwil; Dian Safitri (AT-TAFAHUM: Journal of Law, 2019)
Inheritance law in Indonesia remains pluralistic due to the lack of a unified national inheritance law. Consequently, three legal systems apply: Western inheritance law, Islamic inheritance law, and customary inheritance law. This paper aims to analyze the development of inheritance law, particularly Islamic inheritance law, in court decisions in Indonesia and to examine the concept of statute of limitations in civil law. The method used is a normative juridical approach by examining statutory regulations, the Compilation of Islamic Law, and court jurisprudence. The study's findings indicate that Islamic inheritance law has been reformed through court decisions, reflecting judicial ijtihad (intelligible text) to address social dynamics. These reforms include the recognition of substitute heirs, the status of daughters who may hinder siblings, the implementation of mandatory wills, the granting of rights to children or adoptive parents, and the allocation of a portion to heirs of different faiths through wills or gifts. Furthermore, the principle of deliberation in inheritance distribution has been incorporated to achieve more flexible justice. On the other hand, the concept of a statute of limitations in civil law plays a crucial role as a means of acquiring rights or releasing obligations due to the lapse of a certain period. A statute of limitations can result in the loss of the right to sue in inheritance disputes if it is not exercised within the legally prescribed timeframe.